Bread wastes to energy: Sequential lactic and photo-fermentation for hydrogen production. (17th May 2018) - Adessi, Alessandra; Venturi, Manuel; Candeliere, Francesco; Galli, Viola; Granchi, Lisa; De Philippis, Roberto
Abstract: One third of the World's entire food production is lost or wasted every year. Biohydrogen production offers a possibility to re-use this resource; in particular, bread and bakery products wastes, due to their composition (up to 70% of carbohydrates, mostly starch), represent an appropriate source of nutrients for microorganisms. The aim of this work was to convert bread wastes into hydrogen with a sequential system composed of lactic fermentation and photofermentation, with a minimum number of treatments to the substrate. The best results were provided by Lactobacillus amylovorus DSM 20532, followed by photofermentation by Rhodopseudomonas palustris 42OL, supplemented with ferric citrate and magnesium sulfate. The process led to 3.1 mol H2 mol −1 glucose, among the highest yields obtained on starch containing substrates, with an energy recovery of 54 MJ t −1 dry waste. This study promotes the re-use of energy-containing food wastes for improving circular economy. Highlights: Bread wastes are a suitable substrate for biohydrogen production. Lactobaccillus amylovorus efficiently converted starch into lactate in 18 h at 37 °C. No hydrolytic pretreatment on bread wastes was necessary. Fe(III) and MgSO4 addition significantly improved hydrogen production. Rhodopseudomonas palustris produced 3.1 moL H2 mol −1 glucose.